Alleviation of Brain Hypoperfusion after Preventative Treatment with Lomerizine in an Elderly Migraineur with Aura. (27th December 2010) - Aoyagi, Joe; Ikeda, Ken; Kiyozuka, Tetsuhito; Hirayama, Takehisa; Ishikawa, Yuichi; Sato, Ryuta; Yoshii, Yasuhiro; Kawabe, Kiyokazu; Iwasaki, Yasuo
Abstract : Previous studies of brain single-photon emission tomography (SPECT) showed changes of regional cerebral blood flow (rCBF) in migraineurs during prodromes or headache attacks. Little is known about how successful medication of migraine prevention can reflect rCBF in migraineurs. We highlighted alternation of brain SPECT findings in a migraineur with aura before and after prophylactic treatment with lomerizine, a calcium channel blocker. A 70-year-old man with migraine developed visual disturbance frequently at walking exercise for the recent 3 months. After this visual attack, a mild-degree of throbbing headache occured occasionally. Brain SPECT using 99m Tc-ethyl cysteinate dimer was performed at interictal time of migraine. Brain SPECT before lomerizine treatment revealed hypoperfusion in the frontal, parietal, and occipital regions. He was diagnosed with recurrence of migraine with aura (MA). Lomerizine (10 mg/day, po) was administered for 3 months. MA and visual aura without headache were dramatically improved. Migraine attacks and visual disturbance were not induced at exercise. At 3 months after lomerizine medication, brain SPECT showed remarkable increase of rCBF. These SPECT changes of our patient indicated that antimigraine mechanism of lomerizine could contribute to restoration of cerebral hypoperfusion.